1985
DOI: 10.1002/jcp.1041220216
|View full text |Cite
|
Sign up to set email alerts
|

The osmotic response of human erythrocytes and the membrane cytoskeleton

Abstract: The volumes of human erythrocytes suspended in solutions of varying concentrations of sodium chloride and sucrose were measured by a Coulter Channelyzer Model H4 with appropriate corrections. The cells showed greatly restricted volume changes at osmolarities between 200-700 mOsm. At osmolarities outside this limit, on the other hand, the cells showed nonrestricted volume changes following essentially the predictions of an ideal osmometer. This unexpected volume response was not spuriously due to changes in sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
23
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…The solid points and associated straight line represent the "true" volumes, after having quantitatively corrected the "measured' volumes for shape factor, according to the method of Richieri et al (1985a,b). Since the deviation between the straight line and the raw-data curve in Figure 2 is clearly within the same range as that shown in Figure 1 (and also estimated from other similar plots of Heubusch et al, 1985), it can be stated that the shape factor correction alone can similarly account for the deviations in the hypotonic range of their data.We have found that the same linearization effect also results from the similar correction of other of our osmotic pressure-volume data, taken under different conditions (of temperature, PBS composition, pH, etc.) but at the same slow-flow rate through the orifice.…”
supporting
confidence: 70%
See 3 more Smart Citations
“…The solid points and associated straight line represent the "true" volumes, after having quantitatively corrected the "measured' volumes for shape factor, according to the method of Richieri et al (1985a,b). Since the deviation between the straight line and the raw-data curve in Figure 2 is clearly within the same range as that shown in Figure 1 (and also estimated from other similar plots of Heubusch et al, 1985), it can be stated that the shape factor correction alone can similarly account for the deviations in the hypotonic range of their data.We have found that the same linearization effect also results from the similar correction of other of our osmotic pressure-volume data, taken under different conditions (of temperature, PBS composition, pH, etc.) but at the same slow-flow rate through the orifice.…”
supporting
confidence: 70%
“…In contrast, increased chemical nonideality and eventual hemolysis are the likely factors responsible for the behavior in t h e hypertonic range. Figure 1 reproduces a plot of osmotic volume changes reported by Heubusch et al (1985) for erythrocytes in dilute saline (NaC1) solutions (from Heubusch et al, 1985; Fig. 1).…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…In addition, membrane-skeleton and cell-skeleton proteins can restrain cell swelling [19] and thus interfere with osmotically driven cell fusion. Proteinases are important in chemically induced cell fusion , and the fusion of erythrocytes by some chemical fusogens involves the proteolysis of ankyrin by a serine proteinase [23] and the proteolysis of band 3 by a calcium-activated proteinase [23,24].…”
Section: Perturbation Of Membrane Proteinsmentioning
confidence: 99%